Distribution and molecular characterization of begomoviruses infecting tomato in sub-Himalayan Tarai region of West Bengal and Brahmaputra valley of Assam in northeast India - KAJAL KUMAR BISWAS and ANIRUDDHA SAHA*, BIKRAM SAHA, DIPANWITA SAHA, (Indian Phytopathology, 2014)
Tomato leaf curl disease (TLCD) in tomato of Sub-Himalayan Tarai region of West Bengal and Brahmaputra valley of Assam was surveyed and various symptoms like curling, blistering, crinkling and narrowing of leaves with stunted growth were observed. The estimated incidence was 18-83% in sub-Himalayan West Bengal and 14-71% in Brahmaputra valley of Assam. This disease was transmitted to tomato plants through whitefly (Bemisia tabaci) with transmission efficiency of 50-80%. Five TLCD causing virus isolates COB-2, COB-5, GUW-1, RAI-1 and SILIGURI-2 from these regions were characterized based on sequencing of coat protein (CP) gene of begomovirus genomes. The sequence analysis showed that the present isolates shared 79-98% nt identity among them and 79-99% nt identities with other tomato infecting begomoviruses available in database. The isolates COB2, RAI-1 and SILIGURI-2 were similar to each other and related by 94-99% sequence identity with the isolates of Tomato leaf curl New Delhi virus (ToLCNDV; EU375489, EF043230, JN676054, HM007113, U15016, AM849548, JX232220, AM286434). The isolate COB-5 and GUW-1 are similar and are related with the with Tobacco curly shoot virus (TbCSV; GU001879, JX467693), Tomato leaf curl Ranchi virus (ToLCRnV, GQ994095) and Tomato leaf curl Bangladesh virus (ToLCBnV; AF188481) by 95-98% sequence identity. In phylogenetic analysis, the present isolates formed two clades among them; COB2, RAI-1 and SILIGURI-2 in one and COB-6 and GUW-1 into another clade. The present data suggest that the TLCD in tomato in these regions is caused by a combination of begomoviruses.